Hacia un federalismo competitivo : una propuesta para reformar el sistema de financiación autonómica / Juan F. Corona, Luis M. Alonso, Pedro Puy - Alonso González, Luis ManuelPuy, Pedro; Corona Ramón, Juan Francisco (Monografía; 4)
Bibliografía